Strategy for Developing Creative Thinking Skills in Learning to Write Poetry for Junior High School Students - Kusubakti Andajani; Didin Widyartono; Kusmiati Kusmiati (Jurnal Paedagogy, 2023)
This study aims to describe the strategy for developing creative thinking skills and the functions and benefits of developing creative thinking skills in learning to write poetry for junior high school students. The method used was a descriptive method with a qualitative approach. Data collection was carried out using interviews and questionnaires. The informants in the study were 12 Indonesian Language and Literature learning teachers in the East Java region, including Kediri, Gresik, Malang, Madura, Jombang, Banyuwangi, Lamongan, Kalimantan. The data analysis technique used was discourse analysis, which analyzed oral and written answer sentences. Based on the data, it can be concluded that the learning strategies for writing poetry carried out by teachers were diverse, including word picking, word-priming strategies, word chat cards, cooperative learning (roulette writing), modeling, photos/events that have been experienced, objects, directly seeing things, pictures, word clusters, a combination of models, one event one poem, one picture one poem, ATM, Student Teams Achievement Division (STAD), keyword strategies, one event one poem, word collections, and experiences. From the method used by the teacher, it turned out that it could improve creative thinking skills based on the stages of creative thinking proposed by Torrance, including fluency, flexibility, originality, and detail in choosing themes, diction/word choice, rhymes, typography, imagery, mandate, and the cohesion of stanzas.